Relationship between menarche age and parity with the incidence of uterine myomas - Indryani, Indryani; Mustar, Mustar; Ali, Sarina; Susilawati, Susilawati; Ismawati, Ismawati (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Background: Uterine myomas, or fibroids, are one of the most common benign tumors that occur in women of reproductive age, with a reasonably high prevalence worldwide. However, rarely, potentially malignant uterine myomas can cause a variety of health problems, including excessive menstruation, pelvic pain, fertility disorders, and pregnancy complications. Objective: This study aims to analyze the relationship between menarche age and parity with the incidence of uterine myoma. Methods: Types and design of research the plan used in this exploration is quantitative exploration with a case control approach. The sample consisted of 138 respondents, 102 of whom were mothers who experienced uterine myoma and 36 mothers who did not experience the adverse effects of uterine myoma. Results: The test results measured using the chi-square test were obtained with p-value menarche age = 0.004 and parity p-value = 0.000, meaning that there was a very large relationship between menarche age and parity with the incidence of uterine myomas. Conclusion: It can be concluded that the earlier the age of menarche increases the risk of uterine myoma later in life. In contrast, slower menarche may be associated with a reduced risk of myomas. Other factors such as genetic, environmental, and lifestyle factors also influence the incidence of uterine myomas, but menarche age is one of the significant hormonal indicators of risk